Purification of Sardine Fish Oil Through Degumming and Neutralization - Stephanie Bija; Sugeng Heri Suseno; Uju Uju (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
The quality of sardine fish oil can be improved by purification method through the step of degumming and neutralization. The aimed of this this study was analysis characteristic of crude sardin fish oil and determined the best method of purification. Degumming was carried out using 30% water and salt at concentration 5%, 8%, 10% b/v. Neutralization process using  NaOH with 16°Be and bleaching using 5% Magnesol XL. All step of refining was done at 50°C, 60°C, 70°C, and 80°C. The result of analysis showed that sardine crude fish oil had 24.86% of palmitic acid as the highest fatty acid, heavy metal was not detected,dencity was 0.92 g/cm3 and viscocity was 51 cPs. The best treatment of purification method was degumming using 5% NaCl at 50°C with rendement 65.37±0.72%; free fatty acid (FFA) 0.38±0.03%; peroxide (PV) 1.07±0.12 mEq/kg; anisidine (p-AnV) 15.18±0.16 mEq/kg; total oxidation value (TOTOX) 17.31±0.39 mEq/kg; and clarity was 75.09± 1.20%.